How imagery and brands in luxury perfume advertisements transport the consumer and contribute to the creation of the postmodern symbolic identity - Jessop, Joshua (2018)
This research investigates the ways in which consumers are transported in luxury perfume advertisements through the imagery and brands and how this aids in the crafting of their manifold symbolic identities. It was found that narrative storylines interweave with both the hedonic and experiential elements that occur during the daydreaming process often lived by consumers multiple times throughout the quotidian. Through simulation of the narrative, its imagery and allegories present the consumer was subsequently transported to another reality outside of that in which they were residing. Consequently, this study has expanded the understanding surrounding the ways in which advertising narratives impact consumer psychology and the subsequent crafting of symbolic identity creation. Such a field is vital to explore, as although much extant literature exists on possessions and identity creation, little examines and combines the effects of symbolic transportation of the narrative within the consumer psyche. During the data collection process, in-depth interviews were used to gather data from the selected fourteen female participants. The analysis revealed four main themes: social standing, lifestyle aspirations, the improvement of self-esteem and the perceived sophistication of the French culture. Holistically analysed, these themes highlighted the hedonistic nature of perfume consumption. It became clear that appealing to hidden desires and the notion of the ideal-self were vastly important in engaging the consumers’ imaginations. Such engagement is highly expedient when considering the hybrid nature of the postmodern consumer.